Early adversities accelerate epigenetic aging into adulthood: a 10‐year, within‐subject analysis - Copeland, William E.; Shanahan, Lilly; McGinnis, Ellen W.; Aberg, Karolina A.; Oord, Edwin J.C.G. (Journal of child psychology and psychiatry, 2022)
Background Longitudinal studies are needed to clarify whether early adversities are associated with advanced methylation age or if they actually accelerate methylation aging. This study test whether different dimensions of childhood adversity accelerate biological aging from childhood to adulthood, and, if so, via which mechanisms. Methods 381 participants provided one blood sample in childhood (average age 15.0; SD = 2.3) and another in young adulthood (average age 23.1; SD = 2.8). Participants and their parents provided a median of 6 childhood assessments (total = 1,950 childhood observations), reporting exposures to different types of adversity dimensions (i.e. threat, material deprivation, loss, unpredictability). The blood samples were assayed to estimate DNA methylation age in both childhood and adulthood and also change in methylation age across this period. Results Cross‐sectional associations between the childhood adversity dimensions and childhood measures of methylation age were non‐significant. In contrast, multiple adversity dimensions were associated with accelerated within‐person change in methylation age from adolescence to young adulthood. These associations attenuated in model testing all dimensions at the same time. Accelerated aging increased with increasing number of childhood adversities: Individuals with highest number of adversities experienced 2+ additional years of methylation aging compared to those with no exposure to childhood adversities. The association between total childhood adversity exposure and accelerated aging was partially explained by childhood depressive symptoms, but not anxiety or behavioral symptoms. Conclusions Early adversities accelerate epigenetic aging long after they occur, in proportion to the total number of such experiences, and in a manner consistent with a shared effect that crosses multiple early dimensions of risk.